Experimental Investigation of Using Evaporative Air Cooler for Winter Air-Conditioning in Baghdad - Hassan, Zainab Hasson; Hanash, Zainab Hassan (Al-Khwarizmi Engineering Journal, 2012)
This paper presents an efficient methodology to design modified evaporative air-cooler for winter air-conditioning in Baghdad city as well as using it for summer air-conditioning by adding a heating process after the humidification process. laboratory tests were performed on a direct evaporative cooler (DEC) followed by passing the air on hot water through heat exchanger placed in the coolers air duct exit. The tests were conducted on the 2nd of December /2011 when the ambient temperature was 8.1°C and the relative humidity was  (68%). The air flow rate is assumed to vary between 0.069 to 0.209 kg/s with constant water flow rate of 0.03 kg/s in the heat exchanger. The performance is reported in terms of effectiveness of DEC, saturation efficiency of DEC, outlet temperature of air and cooling capacity. Heat transfer rate in heat exchanger mode is also estimated. The paper presents the mathematical development of the equations of thermal exchanges through DEC and HE. prediction of air condition that exits o this system show that the present system could bring the air stream to a comfortable winter zone .